Association Between Changes in BLyS Levels and the Composition of B and T Cell Compartments in Patients With Refractory Systemic Lupus Erythematosus Treated With Belimumab - Regola, Francesca; Piantoni, Silvia; Lowin, Torsten; Archetti, Silvia; Reggia, Rossella; Kumar, Rajesh; Franceschini, Franco; Airò, Paolo; Tincani, Angela; Andreoli, Laura; Pongratz, Georg (Frontiers in Pharmacology, 2019)
Introduction: Belimumab is a monoclonal antibody against soluble BLyS used for treatment of refractory Systemic Lupus Erythematosus (SLE). Although B cells are the main target of this therapy, a BLyS-dependent T cell activation pathway has also been demonstrated. The aim of the study is to analyze B and T cells phenotype modifications in a cohort of SLE patients treated with belimumab in correlation with serum BLyS levels. Materials and Methods: Fourteen SLE patients were enrolled in the study. Lymphocyte immunophenotyping by flow cytometry and determination of serum BLyS levels by high sensitivity ELISA were performed before the first infusion of belimumab, after six and twelve months of treatment. Sex and age-matched healthy controls were enrolled for the comparisons. Results: Baseline number of total B cells, especially switched memory B cells, were lower in SLE patients compared to control subjects. After 6 months of treatment, the total number of B cells, particularly, naïve and transitional B cells, was significantly reduced in correlation with the reduction of BLyS levels. No significant association was found between baseline count of B cells and reduction of SLEDAI-2K over time. In terms of response prediction, a significant association between SLEDAI-2K improvement at 12 months and the decrease of total number of B cells within the first six months of therapy was observed. Concerning the T cell compartment, the baseline percentage number of CD8+ effector memory was associated with SLEDAI-2K at baseline and with its improvement after 12 months of therapy. Furthermore, T cell lymphopenia and low number of circulating recent thymic emigrants were also observed compared to control subjects measured at baseline. Discussion: The effects of belimumab on B cell subpopulations could be explained by the direct blockage of soluble BLyS, while the mild effects on T cells might be explained indirectly by the reduction of disease activity by means of therapy. B cell immunophenotyping during belimumab might be useful for monitoring the response to treatment.